Unraveling the Roles of Saltation Bombardment and Atmospheric Instability on Magnitude and Size Distribution of Dust Emission Fluxes: Lessons From the JADE and WIND‐O‐V Experiments. Issue 12 (27th June 2022) - Alfaro, S. C.; Bouet, C.; Khalfallah, B.; Shao, Y.; Ishizuka, M.; Labiadh, M.; Marticorena, B.; Laurent, B.; Rajot, J. L.
Abstract: The size distribution of the vertical flux of dust freshly emitted from a wind‐eroded surface was recently shown to depend on the thermal stratification of the surface boundary layer (SBL). These new results question the way dust emission is currently represented in the dust models and emphasize the need to identify the factors controlling the intensity and size‐resolved dust flux at emission. In this study, we re‐analyze the data of two major campaigns (JADE and WIND‐O‐V) performed on unvegetated plots and during which the characteristics of the (a) surface of the eroding fields, (b) aerodynamic conditions (wind speed, stability of the SBL), (c) saltation flux (intensity and size distribution), and (d) vertical dust flux (intensity and size distribution) determined by the gradient method were carefully documented. The magnitude and size distribution of the vertical dust flux are found to be deeply intertwined and to be controlled in the first place by the kinetic energy of the saltating sand grains, and to a lesser extent by the size‐dependent uplift of the sandblasted particles. In unstable conditions coarser sand grains are mobilized, which increases the kinetic energy of the saltation flux and leads to the production of finer particles by sandblasting. Conversely, the uplift of supermicron particles is facilitated by the increase of the wind friction velocity, which results in an enrichment of the vertical dust flux in the coarsest particles at large wind speeds. The implications of these new findings are particularly important for the modeling of the dust emission/transport/deposition cycle. Key Points: During erosion events, vertical dust flux is not linearly proportional to saltation flux The size of emitted dust is controlled by the kinetic energy of the saltating sand grains The vertical dust flux is enriched in fine particles during intense events and in unstable conditions